Studies on type II glycogenosis. Effects of cortisone derivatives on acid α-glucosidase - Bourne, E. J. (1971)
Cortisone causes a marked increase in the activity of liver acid α-glucosidase 2h after injection into male Wistar rats. Studies on rat liver tissue slices, isolated lysosomes and cultured skin fibroblasts have demonstrated similar elevations of acid α-glucosidase activity after incubation with cortisone. Cortisone-treated human liver tissue, obtained by needle biopsy, also shows an increase in acid α-glucosidase activity. Neutral α-glucosidase activity was not stimulated by cortisone in vivo or in liver slices.